Blended Learning Approach in Teaching English Writing Skill at Senior High School - Dwinggrum, Crismin; Dollah, Syarifuddin; Weda, Sukardi (Har Press Indonesia, 2023)
Online educational resources are combined with platforms or locations that simulate traditional classroom settings to create blended learning. Utilizing technology with the intention of achieving the learning process' objective is blended learning implementation. The purpose of this study is to find out the effect of the blended learning approach and to find out the students’ perception on the use of blended learning approach in English writing skill at senior high school the eleventh-grade students of SMA Negeri 13 Makassar, which consists of 6 classes with an average class size of 35 to 36 students, comprised the population of this study. After that, the researcher used the cluster random sampling approach to select 71 students from two classes as the study's subject. Based on the findings of this research, SPSS output for independent sample t-tests, t-test 4,426 is higher than t-table 1,995. The t-test's outcome demonstrates that there is a significant difference between the t-test's score and the t-table's score. This suggests that the treatment has a big impact on how well students can write. According to the questionnaire results, students at SMA Negeri 13 Makassar's eleventh grade have a positive perception of the behavior on the use of blended learning approach to teach English writing in senior high school. . In conclusion, SMA Negeri 13 Makassar's eleventh grade students' writing skills are considerably affected by the use of a blended learning approach.